The Art and Science of Rotating Field Machines Design: A Practical Approach - Ostović, Vlado; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book highlights procedures utilized by the design departments of leading global manufacturers, offering readers essential insights into the electromagnetic and thermal design of rotating field (induction and synchronous) electric machines. Further, it details the physics of the key phenomena involved in the machines' operation, conducts a thorough analysis and synthesis of polyphase windings, and presents the tools and methods used in the evaluation of winding performance. The book develops and solves the machines' magnetic circuits, and determines their electromagnetic forces and torques. Special attention is paid to thermal problems in electrical machines, along with fluid flow computations. With a clear emphasis on the practical aspects of electric machine design and synthesis, the author applies his nearly 40 years of professional experience with electric machine manufacturers - both as an employee and consultant - to provide readers with the tools they need to determine fluid flow parameters and compute temperature distributions.
Introduction.- Windings -- Magnetic Circuit -- Machine Parameters -- Skin and Proximity Effect -- Force and Torque -- Thermal Design of Rotating Field Electric Machines -- General Principles of A.C. Machines Design.
Keywords: Electric power production; Machinery; Industrial organization; Electrical Power Engineering; Machinery and Machine Elements; Industrial Organization